Exploring the Role of a Cytokinin-Activating Enzyme LONELY GUY in Unicellular Microalga Chlorella variabilis - Nayar, Saraswati (Frontiers in Plant Science, 2021)
LONELY GUY has been previously characterized in flowering plants to be involved in the direct activation of cytokinins. In this study, the function of the only LONELY GUY gene (CvarLOG1) from unicellular green microalga Chlorella variabilis NC64A has been investigated. CvarLOG1 expressed mainly in the lag and log phases of growth and was confirmed to be a cytokinin activating enzyme. Overexpression of CvarLOG1 in Chlorella led to extended life in culture by almost 10-20 days, creating a “stay-green” phenotype. In the transformed alga, the cell cycle was lengthened due to delayed entry into the G2/M phase contrary to the known role of cytokinins in stimulating G2/M transition possibly due to excessive levels of this hormone. But due to sustained growth and delayed senescence there was an increase in cell number by 11% and in biomass by 46% at the stationary phase, indicating a potential application for the biofuel industry. The total carbohydrate and lipid yield increased by approximately 30% and 20%, respectively. RNA-Seq based transcriptomic analysis revealed that the genes associated with light and dark reactions of photosynthesis were upregulated, which may be the reason for the increased biomass. These data show that LOG plays an essential role during the cell cycle and in the functioning of the chloroplast. And, that the pathway leading to direct activation of cytokinins via LOG is functional in algae.